The girl with the dragon tattoo - Larsson, Stieg, 1954-2004. (New York : Alfred A. Knopf, 2008)
An unlikely team of investigators discovers a vein of iniquity running through one of the wealthiest families in Sweden and finds an astonishing corruption at the highest echelon of Swedish industrialism.
Originally published: Stockholm : Norstedt, 2005.
Keywords: Journalists -- Sweden -- Stockholm -- Fiction; Missing persons -- Investigation -- Sweden -- Stockholm -- Fiction; Computer hackers -- Sweden -- Stockholm -- Fiction; Swedish fiction -- Translations into English; Stockholm (Sweden) -- Fiction; Mystery fiction